The identity of the contemporary public library - Margarita Pérez Pulido (Ledizioni, 2016)
The volume deals with some of the most relevant issues related to the identity of the public library and its historical, cultural, social, organizational changes, according to a comparative perspective. The topics are covered in four sections (History, Present and Future of the Public Library; Models of Analysis, Measurement, Evaluation; Complexity Challenges; Work in Progress), thus providing a wide overview of the present and the future of an institution paramount in improving people's lives.